TRANSFER OF CODES AND MIXED CODES IN INDONESIAN MOLEBRITIES INSTAGRAM - Iqbal, Muhamad (Bahtera Indonesia, 2021)
This study tries to analyze the code and code mix in Indonesian celebrity Instagram accounts. The research method used is descriptive. Is this research. Then, the source of this research data is uploading on celebrity Instagram accounts from May to June 2020. Meanwhile, the data in this study are the status information uploaded by Indonesian celebrities. Furthermore, collecting data in this study was carried out by making screenshots of uploaded photos or videos accompanied by information and data sourced from Indonesian celebrity Instagram accounts. Then, all the collected text will be categorized by the type of code switching and mixed code. Based on the analysis of research results can be seen as follows. (1) code switching found in the Indonesian celebrity Instagram account caption upload caption over internal code and external code transfer, (2) mixed code found in the Indonesian celebrity idiom Instagram Instagram account caption, and clauses.